Energy and Exergy Analysis of Wet Ethanol-based HCCI Engine Combined Cycle Cogeneration System - Abid Haleem, Shailesh Kumar Trivedi (International Journal of Advanced Science and Technology, 2019)
Homogeneous Charge Compression Ignition (HCCI) engine uses an advance combustion process with a lean premixed air-fuel mixture, and it works with a high compression ratio like a diesel engine. The charge is compression ignited, and ignition occurs throughout the combustion chamber. The present system is proposed to meet the simultaneous demand of power and thermal energy from a sustainable fuel in an efficient and environmentally friendly manner. The paper describes the computational analysis of first and second law efficiencies of wet ethanol-based HCCI engine with a combined cycle cogeneration system by varying its turbocharger efficiency and pinch point. It further describes the exergy destruction in each component and its variation with turbocharger compressor efficiency, pinch point, turbocharger pressure ratio, ambient temperature and effectiveness of regenerator. The cogeneration cycle has a good thermal performance with first and second law efficiencies of 46.47% and 38.5% respectively for the mean operating conditions of  T0=300K, Pr=3, ηT=80% ε=79%. An examination of results indicates that the first and second law efficiencies are increasing function with pinch point of the evaporator of organic Rankine cycle (ORC) as it provides higher exhaust gas temperature at the inlet of HRSG of cogeneration which further results in increasing the quantity of process heat for steam generation. These efficiencies are also increasing with an increase in efficiency of turbocharger compressor because it leads to higher HCCI engine work output due to efficient turbocharger. This study evaluated the thermodynamic losses in terms of exergy destruction, and the same is presented in this paper to answer the reason for deviation on the actual and ideal performance of the system. This paper briefly states the variation in performance of the system due to varying considered parameters. Thus the suitable selection of optimum parameters could yield better performance.